КРЕМНИЙГА ФОСФОР ВА ГАЛЛИЙНИНГ КЕТМА-КЕТ ДИФФУЗИЯСИ НАТИЖАСИДА ГАЛЛИЙ КОНЦЕНТРАЦИЯСИНИНГ ОШИШИ - Зикриллаев, Н.Ф.; Исамов, С.Б. (SCIENCE and SOCIETY, 2021)
The presence of high concentrations of phosphorus during the diffusion of gallium into silicon established the law of a significant increase in the solubility of gallium. The results obtained were explained by the interaction of gallium and phosphorus atoms, and a sharp change in the distribution was found as a result of the action of Coulomb forces.
Keywords: Coulomb interaction; gallium; phosphorus; silicon; solubility distribution